The complementary treatment of endometriosis: diet, physiotherapy and psychological treatment - Agnieszka Siedlak; Monika Kuc; Katarzyna Cyboran; Dominik Machaj; Alicja Płaczek (Kazimierz Wielki University, 2022)
Endometriosis still remains the second most common disease in women of the reproductive period; it occurs in 5-30% of them, including 50% of infertile women and 30% of women with chronic pain in the smaller pelvis. The latest epidemiological data indicating on the increase in the percentage of endometriosis in adolescents (2-5%) and postmenopausal women (3-6%), which is worrying[1]. Diagnostics is the greatest problem of this disease becasue there is no unambiguous blood test which can confirm endometriosis. Moreover, changes are difficult to detect even in imaging examinations, especially in less advanced cases. All of this contributes to delaying diagnosis by up to 10 years. However, there are more and more complementary treatments that can significantly improve the quality of life and reduce the pain.